An evaluation of performance of public sector financial institutions: evidence from Pakistan. (2019) - Haris, Muhammad; HongXing, Yao; Tariq, Gulzara; Malik, Ali
The purpose is to analyse the impact of internal factors and government change on the individual as well as the sector-wide performance of public sector banks of Pakistan. The study employs balanced panel data. The OLS-robust regression is used to examine the impact of internal factors, including Log(TA), LDR, IAR, EQTA, NPLR and government change (GOV), a dummy variable, on the profitability of public sector banks measured by ROA, ROE, PBTR and NOM. To analyse the performance of the overall public banking sector and each bank separately, the graphical method is used. The study reveals indifferent results in terms of government change but reports negative impact of government transition on performance. It also finds NPLR as the most significant factor for the profitability of public sector banks of Pakistan.